Strategi Program Pencegahan Penyalahgunaan Narkoba Pada Badan Narkotika Nasional Provinsi Kalimantan Tengah - Anggelina Hariyanti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
This research aims to determine the strategy of the drug abuse Prevention Program on provincial National Narcotics Agency (BNNP) Central Kalimantan. This research uses a qualitative approach. Data collection techniques consist of primary Data and secondary Data. The data collection techniques in this study are observations, interviews, documentation studies. Data analysis techniques by means of data reduction, data presentation and withdrawal of conclusions. The results showed the drug abuse prevention strategy on the Provincial National Narcotics Agency (BNNP) Central Kalimantan is (1) Demand Side, which is the implementation of information dissemination function and advocacy P4GN to the community. The goal is to increase the public's capture of the dangers of abuse and trafficking in dark drugs among the try (2) Supply Side, strategies taken through the implementation of prevention and eradication of abuse and circulation Dark drugs through the media; Strengthening of therapeutic institutions and rehabilitation of victims of abusers and/or drug addicts in an integrated; and strengthening drug intelligence activities. (3) Central Kalimantan BNNP barrier in implementing drug abuse prevention strategy, among others, a limited number of human resources BNNP Central Kalimantan, lack of public awareness and poor policy on narcotics handling.